Blood pressure control among hypertensive patients of tribal origin attending a primary care centre in Kerala - Raju, Jasmi; Sreedevi, Aswathy; Sasidharan, Navami; Vasudevan, Sanjeev (International Journal Of Community Medicine And Public Health, 2022)
Background: High blood pressure increases the risk for significant health issues including heart attack and stroke. According to studies, the tribal population in India is likewise going through a transformation and has increasing prevalence of high blood pressure. Therefore, this study was done with the objective to determine the proportion of hypertensives with uncontrolled blood pressure among persons of tribal origin attending a primary care centre in Kalpetta, Wayanad, Kerala. To study the factors responsible for the control of hypertension. To assess the adherence to anti-hypertensive medicine using the Morisky Green Levine Scale (MGLS). Methods: A cross-sectional study was conducted at Amrita Kripa Charitable Hospital, Kalpetta, among 167 adult hypertensives of tribal origin. A semi-structured questionnaire and MGLS were used for data collection. Data analysis was done using SPSS version 21. Results: The proportion of uncontrolled hypertension among the tribal population was found to be high (70.7%). There was a significant association with uncontrolled hypertension and lower education (p value 0.036) and also with alcohol (p value 0.007). Among participants with uncontrolled blood pressure, poor adherence was found to be 31.7% while 68.3% of participants had good adherence. Alcohol consumption (aOR- 4.10, 95% CI 1.12-14.98) and lower education (aOR-6.74, 95% CI 1.28-35.46) were independent predictors of uncontrolled hypertension on multivariate analysis. Conclusions: Seven in ten hypertensives attending the primary care centre had uncontrolled hypertension. Larger studies among persons of tribal origin are necessary at the community level through reducing alcohol use is imperative.